Efficient Electrolytes for Lithium–Sulfur Batteries - Angulakshmi, Natarajan; Stephan, Arul Manuel (Frontiers in Energy Research, 2015)
This review article mainly encompasses on the state-of-the-art electrolytes for lithium–sulfur batteries. Different strategies have been employed to address the issues of lithium–sulfur batteries across the world. One among them is identification of electrolytes and optimization of their properties for the applications in lithium–sulfur batteries. The electrolytes for lithium–sulfur batteries are broadly classified as (i) non-aqueous liquid electrolytes, (ii) ionic liquids, (iii) solid polymer, and (iv) glass-ceramic electrolytes. This article presents the properties, advantages, and limitations of each type of electrolytes. Also, the importance of electrolyte additives on the electrochemical performance of Li–S cells is discussed.